A Multi-Theoretical and Multi-Method Family Study Approach to Preschool Inhibitory Control: Links to Working Memory, Receptive Vocabulary, Behavioral Maladjustment, and Parent Mental Health in the Context of Temperament and Executive Functioning Perspectives - Gagne, Jeffrey R.; Barker, Kaelyn; Chang, Chi-Ning; Nwadinobi, Ogechi K.; Kwok, Oi-Man (Frontiers in Psychology, 2021)
Inhibitory control (IC) is defined as the executive functioning (EF) and self-regulatory temperamental inhibition of impulsive or pre-potent behavior and has been consistently linked to multiple forms of childhood cognitive and socio-emotional maladjustment including academic and learning challenges, externalizing behaviors, and attention deficit hyperactivity disorder. However, the results of relevant investigations are somewhat dependent on the method of IC assessment and the theoretical approach of the researcher. The two primary theoretical perspectives on IC are the temperament and the EF approaches, and although there is considerable overlap between these perspectives, there are some distinctions with regard to assessment and emphases on cognition vs. emotion. Therefore, investigations including both temperament and EF approaches to IC are of considerable interest and will best inform future education, prevention, and intervention efforts. This investigation examined associations between child IC, working memory (WM), receptive vocabulary, externalizing behavioral problems, and primary caregiver depression and anxiety symptoms using a family study design. The sample was composed of 99 families with two typically developing preschool children (n = 198; 2.5–5.5 years old; M = 3.88, SD = 1.04) and one primary caregiver/parent. Child IC was assessed using a multi-method approach consisting of one parent-rated questionnaire, three independent observer rating subscales, two videotaped in-person laboratory temperament episodes, and an EF Stroop task. Child WM and receptive vocabulary were measured in the laboratory using standard assessment techniques, and the remaining measures were parent-reported. Male child participants had significantly higher levels of observer-rated hyperactivity and impulsivity, and females had higher levels of observer-rated attention and Stroop-assessed IC. Correlational results showed that excepting IC-Stroop and a snack delay task, all IC measures were significantly correlated. All IC measures except snack delay were positively correlated with WM, and with receptive vocabulary (except Lab-TAB snack delay and observer-rated hyperactivity), and WM and receptive vocabulary were also positively correlated. All IC variables, WM, and receptive vocabulary were significantly related to externalizing behavior problems. Generally, children with higher IC, WM, and receptive vocabulary had lower levels of behavioral maladjustment. Lower parent-rated IC and higher levels of externalizing behavior problems were positively associated with maternal depression and anxiety (lower receptive vocabulary level was related to depression only). Employing structural equation modeling (SEM) analyses, we further examined the interrelationships among IC temperament variables, IC-Stroop, WM, and receptive vocabulary, controlling for age, gender, externalizing behaviors, maternal depression and anxiety, and the parent-rater variance (the multi-method effect). The results of our hypothesized model showed that the IC Temperament factor, composed of the six temperament IC measures, showed a positive effect on receptive vocabulary, while the IC-Stroop positively predicted WM. The IC Temperament factor and IC-Stroop were positively correlated with each other, and the IC Temperament factor, IC-Stroop, WM, and receptive vocabulary were positively related to age. The IC Temperament factor was also associated with fewer externalizing behavior problems, maternal depression had a negative effect on receptive vocabulary, and females showed lower levels of WM and receptive vocabulary than males. Overall, the IC Temperament factor and other covariates together accounted for 22.5% of the variance in vocabulary, whereas IC-Stroop and other controlled variables could explain 49.8% of the variance in WM. These findings indicate that theoretical perspectives (in this case temperament and EF IC contexts) and the different types of assessments used are crucial considerations when interpreting the results of studies of early childhood IC. Although most assessments of IC were associated with the outcomes under study, we found specific associations between temperament measures of IC and receptive vocabulary as well as externalizing, and IC-Stroop and WM. In addition, maternal depression had an effect on receptive vocabulary, emphasizing the developmental importance of family environment in preschool. These findings are relevant to the field of child development because they address several important questions about child EF and self-regulation. 1. Do temperament and EF conceptions of IC differentially predict outcomes? 2. How does the way we measure IC from the EF and self-regulation/temperament perspectives impact our conceptualizations of these important constructs? 3. How can we reconcile the various ways different disciplines define IC and their independence/overlap? 4. How can multi-method and multi-disciplinary perspectives and data collection approaches be combined to better understand both the temperament and EF conceptions of IC? Future studies with this sample will employ this multi-theoretical and multi-method approach on assessment in preschool to predict temperament, EF, and behavioral and academic adjustment in elementary school longitudinally.